Upaya Pembentukan Akhlak Santri melalui Kitab Ta’lim Muta’alim di Pondok Pesantren - Langeningtias, Utari; Taufiq, H. N; Thoifah, I’anatut (Al-Liqo: Jurnal Pendidikan Islam, 2024)
In Islamic boarding schools, students can be monitored directly so that it can facilitate the formation of morals and learning the yellow book as a support for the cultivation of moral education, one of which is the book Ta'lim Muta'alim. Students who have mastered studying the book Ta'lim Muta'alim should be able to implement it in their daily lives. However, many articles were found that were still not working as they should. The aim of this research is to examine how learning the book Ta'lim Muta'alim shapes the morals of students at the Sabilurrosyad Islamic Boarding School in Malang. This research uses qualitative research with a field study approach. This research resulted in an analysis of the learning of the book Ta'lim Muta'alim at the Sabilurrosyad Islamic Boarding School in Malang and an analysis of the factors that influence the formation of santri morals at the Sabilurrosyad Islamic Boarding School in Malang.